Development of Advanced Catalysts for Wastewater Treatment - Duisengalieva, Moldir (Nazarbayev University School of Engineering and Digital Sciences, 2020)
The presence of emerging pollutants in the water bodies is a relatively new environmental concern. Emerging pollutants involves various chemical substances such as pharmaceuticals, disinfection byproducts, gasoline additives and man-made nanomaterials. The problem is increased inefficiency of conventional treatments in Municipal Wastewater Treatment Facilities (MWTF). In the present work, catalytic and photocatalytic processes were applied to caffeine aqueous solutions. Ag modified zeolites and Fe-doped TiO2 catalysts were synthesized. Ag modified zeolites were studied using XRD, XRD, TEM, and SEM analysis. The catalytic and photocatalytic efficiency of all catalysts were examined by pH measurements, Total Carbon (TC) analysis and High-performance liquid chromatography (HPLC). Each experiment lasted for 150 minutes and each 30 minutes taken samples were sent to analysis. For Ag modified zeolites ultraviolet light with 254 nm was used, while for Fe – doped TiO2 catalysts 365 ultraviolet lamp with 365 nm was used. The concentration of caffeine solution was 30 ppm and the volume of the photocatalytic reactor was 500 ml. The first part of the work was devoted to examine catalytic and photocatalytic efficiency of Ag modified zeolites. The application of ultraviolet light without catalysts achieved 5 % caffeine removal showing the high resistance to ultraviolet light. The overall caffeine removal with all samples of Ag modified zeolites was low (15-20%). In the adsorption process, the highest removal of caffeine was obtained by Ag2O_NZU catalyst and in the photocatalytic process; it was achieved by Ag0_NZU catalyst. The study results illustrate the complexity of caffeine structure and the presence of intermediates. The second part of the work was dedicated to examining the photocatalytic activities of the synthesized Fe-doped TiO2 catalysts with different iron concentrations (0.5%, 1%, 2%, 4%). The efficiency of photocatalysts were compared with TiO2 (Degussa P-25) catalyst. The mineralization of caffeine was successfully obtained by using all catalysts. However, TC removal of all catalysts was lower as TiO2. The obtained results also illustrated the presence of intermediates and not completely degradation of caffeine molecule into carbon dioxide.
Keywords: Total Carbon; High-Performance Liquid Chromatography; Ultraviolet light; Scanning Electron Microscopy; Transmission Electron Microscopy; X-ray powder Diffraction; XRD; X-ray Fluorescence; Research Subject Categories::TECHNOLOGY